Intravenous anesthetic propofol binds to 5‐lipoxygenase and attenuates leukotriene B4 production. Issue 4 (9th January 2017) - Okuno, Toshiaki; Koutsogiannaki, Sophia; Ohba, Mai; Chamberlain, Matthew; Bu, Weiming; Lin, Fu‐Yan; Eckenhoff, Roderic G.; Yokomizo, Takehiko; Yuki, Koichi
Abstract : Propofol is an intravenous anesthetic that produces its anesthetic effect, largely via the GABAA receptor in the CNS, and also reduces the N ‐formyl‐methionyl‐leucyl‐phenylalanine (fMLP)‐induced neutrophil respiratory burst. Because fMLP‐stimulated neutrophils produce leukotriene (LT)B4, we examined the effect of propofol on LTB4 production in vivo and in vitro . Cecal ligation and puncture surgery was performed in mice, with or without exposure to propofol. Propofol attenuated the production of 5‐lipoxygenase (5‐LOX)‐related arachidonic acid (AA) derivatives in the peritoneal fluid. Also, in the in vitro experiments on fMLP‐stimulated neutrophils and 5‐LOX‐transfected human embryonic kidney cells, propofol attenuated the production of 5‐LOX‐related AA derivatives. Based on these results, we hypothesized that propofol would directly affect 5‐LOX function. Using meta ‐azi‐propofol (Azi Pm ), we photolabeled stable 5‐LOX protein, which had been used to solve the X‐ray crystallographic structure of 5‐LOX, and examined the binding site(s) of propofol on 5‐LOX. Two propofol binding pockets were identified near the active site of 5‐LOX. Alanine scanning mutagenesis was performed for the residues of 5‐LOX in the vicinity of propofol, and we evaluated the functional role of these pockets in LTB4 production. We demonstrated that these pockets were functionally important for 5‐LOX activity. These two pockets can be used to explore a novel 5‐LOX inhibitor in the future. —Okuno, T., Koutsogiannaki, S., Ohba, M., Chamberlain, M., Bu, W., Lin, F.‐Y., Eckenhoff, R. G., Yokomizo T., Yuki, K. Intravenous anesthetic propofol binds to 5‐lipoxygenase and attenuates leukotriene B4 production. FASEB J . 31, 1584–1594 (2017) www.fasebj.org